Semiotics analysis on “Samsung x BTS: Galaxy for the Planet” Advertisement - Vidiyawati, Anisa Viyata Suci; Wibowo | SINTA ID: 6679378, Arif Ardy (COMMICAST, 2023)
This paper aim to analyze the message from the Samsung x BTS Ads: Galaxy for the planet. Global warming is a form of ecosystem imbalance on earth due to increasing the average temperature of the atmosphere, sea, and land on earth.  Samsung and BTS works together in this Ads to show some concern about environment.  This research uses descriptive qualitative type. The qualitative descriptive method is a research method based on the post-positivism philosophy. Therefore, researchers have analyzed objects and examined each icon, indexical, and symbol to be observed with three aspects of Pierce's Object theory. According to Pierce, semiotics is a science that discusses signs and the production of their meanings.  At this stage, the researcher will discuss the results and research data regarding the problems described, namely the Semiotic Analysis of Samsung x BTS: Galaxy for the Planet advertisements. This advertisement has meaning and message to change people's mindset towards the earth to be more concerned about the environment. This ad also displays symbols and signs. As an electronic brand, Samsung pays more attention to the surrounding environment by using recycled material to minimize environmental impact and carefully chooses its brand ambassador to add value to its ads.